ANALISIS PREFERENSI KONSUMEN MEMILIH PRODUK PARFUM LEMBROU - Zakiyyah, Mutiara Indah; Sienatra, Krismi Budi (Ma Chung Press, 2024)
This research aims to measure consumer preferences for Lembrou product attributes which aim to develop the company's new products. This research method uses a conjoint analysis approach. Where this research uses 16 stimuli to be tested, this research also uses five attributes in producing these stimuli, consisting of: 1). Aroma, 2). Packaging, 3). Durability. 4). Price, 5). Size. The results of the research conducted show that the first attribute (Aroma) is considered the most important first, then the second most important attribute is the Price attribute, then the third attribute is durability, while the fourth attribute is occupied by the packaging attribute, and the last is the size attribute. Not only from the five attributes, the author also measured 16 stimuli, and obtained the best results in the 12th stimulus with the citrus aroma attribute in the second attribute level position, and this data also showed that the endurance attribute obtained the 3-4 hour attribute level that consumers wanted. where the attribute level occupies the first attribute level. Next, the price attribute obtains attribute level data of 40-75k where the attribute level in the data occupies the first position, and the last data is placed on the perfume bottle size attribute where potential customers want the size of their perfume to be 100 ml, then at the 100 ml attribute level it occupies the fourth attribute level , and finally circle packaging occupying the second attribute level.